Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.5877
|View full text |Cite
|
Sign up to set email alerts
|

THU0478 Determination of comorbidities in fibromyalgia syndrome

Abstract: BackgroundAlthough fibromyalgia syndrome is diagnosed by excluding other possible diagnosis based on the patient's clinical features, in recent the studies, it was shown that comorbid diseases affect the course of fibromyalgia.ObjectivesThe aim of this study is to evaluate the comorbid diseases of patients with fibromyalgia and to determine the rates of comorbid diseasesMethodsIn this study, age, gender and comorbid diseases of patients above 18 years and diagnosed with fibromyalgia by a were evaluated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Clinical studies have shown the presence of widespread cerebral blood flow dysfunction in hypertension, especially in patients not receiving any antihypertensive treatment or with inadequate antihypertensive therapy applied (Ripp and Rebrova, 2021). On the other hand, analysis of 509 patients with FM revealed that 187 of them (36.7%) were diagnosed with cardiovascular disease (Bilge et al, 2017); in a different study in 941 patients aged 18-87 years (with an established FM diagnosis) circulatory disorders were revealed and observed in the surveyed age groups as follows: 18-29 years old -28 people (3%), 30-39 years old -39 people (4.2%), 40-49 years old -92 people 9.8%), 50-59 years old -101 people (10.8%), 60-69 years old -33 people (3.5%), 70-87 years old -6 people (0.6%), which indicates predominance of such disorders in adults suffering from FM (Häuser et al, 2019). Chronic headache in FM has also been reported (Kleykamp et al, 2021), with suggestions that FM may be a manifestation of idiopathic intracranial hypertension (Altaraqji et al, 2021).…”
Section: The Relationship Between Hypertension and Neck Fibromyalgiamentioning
confidence: 99%
“…Clinical studies have shown the presence of widespread cerebral blood flow dysfunction in hypertension, especially in patients not receiving any antihypertensive treatment or with inadequate antihypertensive therapy applied (Ripp and Rebrova, 2021). On the other hand, analysis of 509 patients with FM revealed that 187 of them (36.7%) were diagnosed with cardiovascular disease (Bilge et al, 2017); in a different study in 941 patients aged 18-87 years (with an established FM diagnosis) circulatory disorders were revealed and observed in the surveyed age groups as follows: 18-29 years old -28 people (3%), 30-39 years old -39 people (4.2%), 40-49 years old -92 people 9.8%), 50-59 years old -101 people (10.8%), 60-69 years old -33 people (3.5%), 70-87 years old -6 people (0.6%), which indicates predominance of such disorders in adults suffering from FM (Häuser et al, 2019). Chronic headache in FM has also been reported (Kleykamp et al, 2021), with suggestions that FM may be a manifestation of idiopathic intracranial hypertension (Altaraqji et al, 2021).…”
Section: The Relationship Between Hypertension and Neck Fibromyalgiamentioning
confidence: 99%
“…Rheumatic diseases are often associated with a large number of comorbidities, 39 , 40 which are not always treated alongside the main disease. 41 These comorbidities may vary widely and include gastrointestinal problems, headaches, cardiovascular diseases, depression, or other diseases of the musculoskeletal system, and so on.…”
Section: Multimodal Treatment Conceptsmentioning
confidence: 99%
“…Endocrinopathies, rheumatologic diseases, kidney diseases and mental health problems are some of the diseases linked with vitamin D deficiency among the individuals. 7,8 Vitamin D deficiency among the patients suffering from both fibromyalgia and other rheumatologic diseases has been frequently documented in the scientific literature. Makrrani et al concluded that vitamin D deficiency was more prevalent in fibromyalgia patients as compared to the controls.…”
Section: Introductionmentioning
confidence: 99%